Aerodynamic Characteristics of Gas Engine Compressor Under Different Surface Roughness Conditions - RONG, LOO KAI (IRC, 2017)
The objective of this study is to perform investigation on aerodynamic characteristics of gas engine compressor through computational simulation under different blade surface roughness. The study is conducted through mathematical modelling and computer aided simulations. The studied compressor is a CMe2 Experimental Compressor. A mathematical model for compressor was developed. The effect of roughness on the aerodynamic characteristic will be investigated. The roughness is defined as wall roughness height with the roughness coefficient above corresponds to their respective height of 12, 180, 300, 425 and 850 microns with 0 microns as the smooth wall when the simulation is being set up in ANSYS FLUENT. From the study, it was found that the higher the coefficient of roughness of the blades, the lower the efficiency of the compressor. In addition, it was found that the surface roughness coefficient has negligible effect which leads to compressor axi-symmetrical stalling in stable flow conditions. However, the model can be used to predict the likelihood of the compressor experiencing stalling effect with the number of surges in mass flow rate difference between inlet and outlet of compressor. The research has provided us an overview of the characteristics of axi-symmetrical stalling condition of a compressor in a gas turbine engine which can aid future researchers and compressor engineers to understand and enhance gas turbine compressors efficiency and to prevent accidents and disasters that happen due to turbine compressor stalls.